2018
DOI: 10.1080/2162402x.2018.1500674
|View full text |Cite
|
Sign up to set email alerts
|

Actin stabilizer TAGLN2 potentiates adoptive T cell therapy by boosting the inside-out costimulation via lymphocyte function-associated antigen-1

Abstract: Correct temporal and spatial control of actin dynamics is essential for the cytotoxic T cell effector function against tumor cells. However, little is known whether actin engineering in tumor-targeted T cells can enhance their antitumor responses, thereby potentiating the adoptive T cell therapy. Here, we report that TAGLN2, a 22-KDa actin-stabilizing protein which is physically associated with lymphocyte function-associated antigen-1 (LFA-1), potentiates the OTI TCR CD8+ T cells to kill the intercellular adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…This in turn attenuated overall CTL killing activity. Forced over-expression of the dual actin and LFA-1 binding protein TGLN2 in CTL yielded stronger killing activity in case of ICAM-1-expressing but not ICAM-deficient antigen-presenting tumor cells [162]. This observation suggested TGLN2-dependent inside-out activation of LFA-1.…”
Section: Leukocyte/target Cell Interactionmentioning
confidence: 87%
“…This in turn attenuated overall CTL killing activity. Forced over-expression of the dual actin and LFA-1 binding protein TGLN2 in CTL yielded stronger killing activity in case of ICAM-1-expressing but not ICAM-deficient antigen-presenting tumor cells [162]. This observation suggested TGLN2-dependent inside-out activation of LFA-1.…”
Section: Leukocyte/target Cell Interactionmentioning
confidence: 87%
“…*P < 0.05; **P < 0. [17]. Indeed, LFA-1 is an essential initiator for the formation of the IS between cytotoxic T cells and cancer cells, and it mediates the polarization of cytotoxic granules toward target cells via tight adhesion to the target cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, its upregulation is correlated with the clinical stage, tumor size, and invasion in a wide spectrum of cancers [ 15 ]. We previously found that transgelin-2 is also expressed in lymphocytes and functions to stabilize the immunological synapse, thereby enhancing T cell activation [ 16 , 17 ]. It is also involved in filopodium initiation and/or elongation presumably by interfering with the interaction between the Arp2/3 complex and actin [ 18 ], which may drive the enhanced phagocytic behavior of macrophages toward invading bacteria [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAGLN2, an actinbinding protein, can regulate cell morphology, movement and transformation by binding to actin. TAGLN2 is abnormally expressed in a variety of cancers (18), and its deregulation is considered to be correlated with tumorigenesis and tumor development. In gliomas, TAGLN2 is a potential oncogenic factor, which is regulated by TGFβ2 to promote glioma invasion and growth (19).…”
Section: Discussionmentioning
confidence: 99%